The international transfer of capital and the propagation of domestic disturbances under alternative payment system - MODIGLIANI, F.; ASKARI, H. (PSL Quarterly Review, 2013)
Faced with the two extremes of fixed and rigid parities on the one hand, and a system of floating rates on the other, many economists have proposed a system based on official sliding parities. According to this line of reasoning, floating exchanges is unachievable politically and therefore this solution would be the maximum concession towards floating that one may hope to negotiate. In this paper, the authors develop a different argument in favour of sliding pegs as compared to either extremes and conclude that such a system combines the advantages of short-run fixity in mitigating propagation of cyclical disturbances with long-run or structural changes in surplus or deficit. JEL: E42, F33